Effects of the High-Probability Instructional Sequence in Children With Feeding Disorders: A Synthesis. Issue 6 (November 2020) - Silbaugh, Bryant C.; Calderon, Gabriela A.; Eslava, Varsovia Hernandez
The high-probability (high-p) instructional sequence is an intervention commonly used to increase compliance in a variety of skill domains, including compliance with low-probability (low-p) mealtime demands in children with pediatric feeding disorders. However, the effects of the high-p sequence on feeding have varied across studies, a systematic synthesis of the literature to guide practice and further research is lacking, and whether the high-p sequence, as an intervention for feeding problems, meets current evidence-based practice standards in special education is unknown. First, we conducted a systematic multistep search, identified seven studies that met inclusion criteria, and synthesized participant and study characteristics. Then we compared the evidence with the 2014 Council for Exceptional Children (CEC): Standards for Evidence-Based Practices in Special Education. The results suggest that (a) the high-p sequence can improve compliance with low-p mealtime demands in young children with feeding disorders but that more research is needed to clarify relevant contexts and for whom the intervention is likely to be effective, (b) additional research should examine the effects of the high-p sequence on feeding in older children or adults with disabilities as more intrusive procedures based on escape extinction become inappropriate, and (c) the evidence falls short of meeting the CEC standards for an evidence-based practice. We conclude with preliminary practice guidelines.